Abnormal Asymmetry of Brain Connectivity in Schizophrenia - Ribolsi, Michele; Daskalakis, Zafiris J.; Siracusano, Alberto; Koch, Giacomo (Frontiers in Human Neuroscience, 2014)
Abstract Recently, a growing body of data has revealed that beyond a dysfunction of connectivity among different brain areas in schizophrenia patients, there is also an abnormal asymmetry of functional connectivity compared with healthy subjects. The loss of the cerebral torque and the abnormalities of gyrification, with an increased or more complex cortical folding in the right hemisphere may provide an anatomical basis for such aberrant connectivity in schizophrenia patients. Furthermore, diffusion tensor imaging studies have shown a significant reduction of leftward asymmetry in some key white matter tracts in schizophrenia patients. In this paper, we review the studies that investigated both structural brain asymmetry and asymmetry of functional connectivity in healthy subjects and schizophrenia patients. From an analysis of the existing literature on this topic, we can hypothesize an overall generally attenuated asymmetry of functional connectivity in schizophrenia patients compared to healthy controls. Such attenuated asymmetry increases with the duration of the disease and correlates with psychotic symptoms. Finally, we hypothesize that structural deficits across the corpus callosum may contribute to the abnormal asymmetry of intra-hemispheric connectivity in schizophrenia.